Histological Changes Induced by Organophosphate Chlorpyrifos in Liver Tissue of Adult Male Rabbits - EL Daffri, Hanan; Mohammed , Najat M.H.; Amraje, Fatma; Khaled , Fyrouz; Ali , Alnagy Mohammad (Scientific Journal of University of Benghazi, 2022)
Background: Chlorpyrifos (CPF) is one of the most common pesticides that is extensively applied in agriculture and animal houses. Several experimental studies on rats demonstrated that exposure to CPF elicits a group of deleterious effects including hepatic dysfunction, immunological defect and neurotoxicity. Moreover, there is concern regarding their deleterious effects on human life. This study investigated the influence of chlorpyrifos on the hepatic tissue of adult male rabbits in long-term exposure and evaluated the protective role of vitamin E in ameliorating toxic impacts. Methods: Twenty adult male rabbits were used in the study. Their average weight was (27.6 ±1.891) Kg. They were divided into four groups, five animals in each. The control group received only distilled water. The CPF-treated group was administrated 33.3mg/Kg of insecticide orally by gastric gavage. The vitamin E group received only Vit E; 150mg/kg body weight. Animals in the combination group were treated with CPF and given Vit E at the same time. The treatment was applied once daily in the morning after a food supplement for 12 weeks. Animals were then anesthetized with chloroform, their livers were removed, placed in formalin, processed and stained with hematoxylin and eosin, and with Masson's trichrome Results: Histopathological changes showed that CPF caused degenerative changes in hepatocytes in terms of vacuolization of cytoplasm, congestion, dilatation of the sinusoidal lumen, and leukocytic infiltration of liver parenchyma, as well as the presence of signs of fibrosis manifested by trichrome stain indicating the chronic effect of pesticides. In the combination group, the majority of hepatocytes presented with normal structures, and the amount of fibrosis was diminished around the portal area. Additionally, congestion appeared to a milder degree than in the experimental group, suggesting the antioxidant role of vitamin E in reducing toxic effects. Conclusion: The study concluded that CPF could cause hepatocellular damage to the rabbits' tissue which can be alleviated by applying antioxidants such as vitamin E.